Association between mobile phone addiction and social support among mainland Chinese teenagers: A meta-analysis - Wan, Xiao; Huang, Haitao; Jia, Ruiying; Liang, Dandan; Lu, Guangli; Chen, Chaoran (Frontiers in Public Health, 2022)
Background Mobile phone addiction brings many adverse effects to teenagers, such as physical health problems, emotional problems, and academic failure, and studies have found that social support is an important influencing factor. Therefore, considering institutional, cultural and economic differences, we aimed to investigate the association between mobile phone addiction and social support among mainland Chinese teenagers, and explored the moderators affecting the relation. Methods Based on the PRISMA method, a meta-analysis was applied to quantitatively synthesize relevant findings to obtain reliable estimates of effect sizes and conduct moderator analyses. Results In total, 92 studies involving 59,716 participants and 92 effect sizes were identified by a systematic literature search. A significant low degree of negative correlation was found between mobile phone addiction and social support (r = −0.174, 95%CI = −0.213 to −0.134, p < 0.001, I2 = 96.1%). Moreover, the present meta-analysis observed significant moderating effects of participants' gender, and region on the association between social support and mobile phone addiction. Conclusion This study suggests that the mobile phone addiction level of teenagers could be reduced by increasing social support, and actions to improve their social support levels should be proposed based on their gender and regional differences. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021276672.